Everolimus‐eluting stents and zotarolimus‐eluting stents for percutaneous coronary interventions. Issue 7 (8th March 2013) - Hannan, Edward L.; Zhong, Ye; Wu, Chuntao; Walford, Gary; Holmes, David R.; Jacobs, Alice K.; Stamato, Nicholas J.; Venditti, Ferdinand J.; Sharma, Samin; Fergus, Icilma; King, Spencer B.
<x xml:space="preserve">Abstract</x> Objectives To compare 2‐year outcomes (mortality, mortality/myocardial infarction (MI), target vessel PCI (TVPCI), and target lesion PCI (TLPCI)) for patients receiving EES and ZES. Background The utilization of drug‐eluting coronary stents (DES) among patients undergoing percutaneous coronary interventions (PCI) has increased dramatically in the last decade. Everolimus‐eluting stents (EES) and ENDEAVOR zotarolimus eluting stents (ZES) constitute the latest generation of approved DES in the United States, but little is known about their relative effectiveness. Methods New York patients undergoing EES and ZES revascularization without any other type of stent between 7/08 and 12/08 were propensity matched at the hospital level using multiple patient, operator, and hospital characteristics, and matched patients were followed through the end of 2010 to obtain comparative 2‐year outcomes. Results A total of 3286 patients were propensity‐matched. Patients receiving EES had a significantly lower TVPCI rate (9.0% vs. 11.9%, AHR = 1.31, 95% CI (1.04, 1.65)) and a significantly lower TLPCI rate (6.0% vs. 8.3%, AHR = 1.35, 95% CI (1.02, 1.79)). There was no significant difference between EES and ZES for mortality or MI/mortality. Conclusions There were no significant differences in the hard endpoints of death or MI between patients who received EES versus those who received ZES (ENDEAVOR). Patients with EES experienced lower repeat revascularization rates than patients with ZES at 24 months. © 2012 Wiley Periodicals, Inc.